The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.ajic.2014.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis on central line–associated bloodstream infections associated with a needleless intravenous connector with a new engineering design

Abstract: The NC with an improved engineering design is associated with lower CLA-BSI risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…a lack of studies in general, non-randomisation and a lack of peer-reviewed publications being included in the meta-analysis. It is interesting to note that just as the FDA (2010) were issuing their notice regarding positive displacement NCs, data collection on the encouraging effects of positive displacement NCs was being completed by Tabak et al (2014). Thus, the 'improved engineering design' mentioned was actually being used as early as 2006, and five of the seven studies had completed data collection at least 12 months before the FDA released its alert.…”
Section: The Consequences 4: Purchasers Stopped Using Positive Displamentioning
confidence: 99%
See 3 more Smart Citations
“…a lack of studies in general, non-randomisation and a lack of peer-reviewed publications being included in the meta-analysis. It is interesting to note that just as the FDA (2010) were issuing their notice regarding positive displacement NCs, data collection on the encouraging effects of positive displacement NCs was being completed by Tabak et al (2014). Thus, the 'improved engineering design' mentioned was actually being used as early as 2006, and five of the seven studies had completed data collection at least 12 months before the FDA released its alert.…”
Section: The Consequences 4: Purchasers Stopped Using Positive Displamentioning
confidence: 99%
“…The Tabak et al (2014) study (on which Jarvis is a coauthor) was a meta-analysis of available studies comparing the MaxPlus®, with those NCs which were in current use; researchers found a lower CLABSI with the MaxPlus® (Tabak et al, 2014). Only one of the available studies found was in a peer-reviewed journal, the remaining six studies were found from conference abstracts.…”
Section: The Consequences 4: Purchasers Stopped Using Positive Displamentioning
confidence: 99%
See 2 more Smart Citations
“…Adequate cleaning or need for additional cleaning of the septal access site may be based on the specific design features of the individual NC [2,4,5,7,70,111,129,153,[159][160][161]. New products or technology should be transitioned into a healthcare facility only after a complete evaluation of both the research and the performance of the product to determine the impact of the change on patient outcomes [71,97,98,149,160,[162][163][164][165][166].…”
Section: Why Disinfect?mentioning
confidence: 99%